Peptide antisera targeted to a conserved sequence in poliovirus capsid VP1 cross-react widely with members of the genus Enterovirus. - Hovi, T (1993)
Rabbits were immunized with synthetic peptides derived from an immunodominant region of the VP1 capsid protein of enteroviruses. This region shows a high degree of homology among all sequenced members of the genus. Peptide-induced antisera were used for immunoperoxidase staining of cell cultures infected with 41 different serotypes of enterovirus. Specific cytoplasmic staining was readily seen in all but two cases. Echovirus type 22 was previously known to differ genetically from the rest of the enteroviruses, and hence, a negative result was expected. Surprisingly, one of the tested serum samples reacted with echovirus 22-infected cells. Coxsackievirus A7-infected cells could be reliably stained with only one of the tested serum samples. For the remaining 39 serotypes, scattered infected cells resulting from 1 to 2 days of incubation with diluted inocula were easily scored as positive before the cytopathic effect became visible. The same antibodies were also used in a sandwich-type enzyme immunoassay to demonstrate poliovirus antigens in cell extracts as early as 3 h after a high-multiplicity infection. These antibodies are candidates for enterovirus group reagents, being potentially useful in both the laboratory diagnosis of enterovirus infections and research on enterovirus-host interactions.